2018
DOI: 10.1590/1678-4324-2017160572
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the Magnetic Nanoparticles with Alkaline Protease Enzyme Produced by Enterococcus hirae and Pseudomonas aeruginosa Isolated from Dairy Effluents

Abstract: Protease is an enzyme which has a wide range of applications in various fields. Extracellular protease was produced from Pseudomonas aeruginosa and Enterococcus hirae which were isolated from the effluents of diary industries. Protease immobilized with super paramagnetic nanoparticles was characterized by DLS, XRD and TEM methods in relation to their size and structure. The protease enzyme was bound to magnetic nanoparticles via surface transformation technique including Silica coated magnetic Nano composite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Al-Dhabi-82 was reported by Al-Dhabi et al ( 2020 ). Similarly, Masi et al ( 2017 ) reported alkaline protease production from Enterococcus hirae and Pseudomonas aeruginosa isolated from dairy effluents. They further carried out formation of nanocomposite of the bacterial protease with super paramagnetic nanoparticles leading to protease stability enhancement.…”
Section: Alkaline Proteasesmentioning
confidence: 94%
“…Al-Dhabi-82 was reported by Al-Dhabi et al ( 2020 ). Similarly, Masi et al ( 2017 ) reported alkaline protease production from Enterococcus hirae and Pseudomonas aeruginosa isolated from dairy effluents. They further carried out formation of nanocomposite of the bacterial protease with super paramagnetic nanoparticles leading to protease stability enhancement.…”
Section: Alkaline Proteasesmentioning
confidence: 94%
“…The plates were observed for the zone of proteolysis around the inoculated wells. The enzymes which show a high zone of hydrolysis are selected and cultured in nutrient broth medium and also preserved in agar slants at 4°C for further studies (Sneha et al 2014, Masi et al 2017a).…”
Section: Secondary Screening Of Potential Alkaline Proteaseproducing Bacteriamentioning
confidence: 99%
“…Enzymes have better catalytic efficiency, adjustable activity, and high specificity when compared to catalysts of chemical or synthetic origin. These advantages have broadened the application of enzymes in various industries such as chemical, food, and pharmaceutical (Pires-Cabral et al 2010;Yucel 2012;Masi et al 2017a). This has generated a greater demand for enzyme production of high quality by cost-effective and commercial methods.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme shows Brownian movement in aqueous solution when bounded with nanoparticles. Additionally, there is an additional advantage for magnetic nanoparticles as it can be separated easily using a magnetic field (Neda et al 2019;Masi et al 2017). The advantage of nanoparticles in immobilization is that it can improve stability and performance and reduce protein unfolding other advantages and disadvantages listed in Table 9.…”
Section: Enzyme Immobilization On Nanoparticlesmentioning
confidence: 99%